USM LEGAL ADVISOR SOLE REPRESENTATIVE OF MALAYSIA AT IIEP - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
Universiti Sains Malaysia (USM) Legal Advisor and Certified Integrity Officer (CeIO), Khairul Anuar Che Azmi has made the university and the country proud by becoming the sole representative to be offered an invitation by the International Institute for Educational Planning (IIEP), an institution under UNESCO based in Paris, to present a working paper based on his experience and expertise.